Educação em saúde em comunidades quilombolas - Rodrigues, Sabrina Alessandra [UNESP]; Lucas, Matheus Guilherme [UNESP]; Cerqueira, Shara Tabita da Silva [UNESP]; Braga, Aparecida da Silva; Vaz, Luis Geraldo [UNESP] (My University, 2011)
To appraise the oral health knowledge of parents and children from the quilombola communities located in the Ribeira Valley, Sao Paulo. Methods Preventive and educational activities in oral health were developed with children in the communities (Andre Lopes, Ivaporunduva, Pedro Cubas and Sapatu) including lectures, guidance on tooth brushing techniques, supervised mass brushing, detection of tooth biofilm and topical application of fluoride. Parents also participated in the activities. They were evaluated on the oral health of their children by means of a standard questionnaire. The water supply of the communities was also analyzed. Results The children participated enthusiastically and responsively in the preventive and educational activities. As to the questionnaires, 56% of parents stated that their children’s oral health was poor and 47.2% of them usually follow up on their children’s oral hygiene until they are approximately six years old, but this follow-up is not frequent. Conclusion We conclude that quilombola parents and children have very little knowledge about oral health. Therefore increased attention to oral health is required in these communities by means of frequent oral health education and promotion.

Avaliar o conhecimento sobre saúde bucal dos pais e filhos presentes nas comunidades quilombolas localizadas na região do Vale do Ribeira, São Paulo. Métodos Foram desenvolvidas nas comunidades (André Lopes, Ivaporunduva, Pedro Cubas e Sapatu) atividades educativas e preventivas sobre saúde bucal com as crianças, por meio de palestras, orientações de técnica de escovação, escovação em massa supervisionada, revelação de biofilme dental e aplicação tópica de flúor. Os pais das crianças também participaram das atividades em que foram avaliados sobre a saúde bucal de seus filhos, por meio da aplicação de um questionário padronizado. Além disso, também foi realizada a análise da água de abastecimento das comunidades. Resultados As crianças apresentaram-se entusiasmadas, receptivas e participativas durante o desenvolvimento das atividades educativas e preventivas. Sobre a aplicação dos questionários, 56,0% dos pais declaram que é ruim a saúde bucal dos seus filhos e 47,2% costumam acompanhar a higienização bucal até os seis anos de idade, aproximadamente, sendo que esse acompanhamento não é frequente. Conclusão Concluiu-se que pais e filhos quilombolas possuem pouco conhecimento sobre saúde bucal, assim observa-se à necessidade de maior atenção à saúde bucal nessas comunidades, por meio de frequentes ações de educação e promoção de saúde bucal.
Health education in quilombola communities
Keywords: Children; Health education; Oral health; Crianças; Educação em saúde; Saúde bucal